Pleuroscopic cryoprobe biopsies of the pleura: A feasibility and safety study. Issue 2 (5th December 2014) - Thomas, Rajesh; Karunarathne, Shanka; Jennings, Barton; Morey, Sue; Chai, Siaw Ming; Lee, Y.C. Gary; Phillips, Martin J.
Abstract Background and objective Flexi‐rigid pleuroscopy is a useful tool in the work‐up of pleural effusions, but pleural biopsy using flexible forceps can be difficult in some patients. This study evaluated the feasibility, safety and diagnostic value of using a flexible cryoprobe to obtain parietal pleural biopsies during pleuroscopy. Methods This was a single‐centre retrospective study. In patients undergoing diagnostic pleuroscopy, pleural biopsy using flexible forceps, followed by a flexible cryoprobe introduced through the pleuroscope, were performed. A pathologist independently reviewed all biopsies. Any complications, particularly bleeding, were recorded. All patients were followed up for ≥6 months (median 12 months (range 7–26)). Results Twenty‐two patients (21 males; median age 72 years; 14 right‐sided effusions) were included. All underwent flexible forceps biopsies (FFB) and cryoprobe biopsies (CB) of pleura. FFB and CB established a definitive diagnosis in 20/22 (90%). CB successfully obtained pleural tissue suitable for histopathological analysis in all patients. CB was larger than FFB (median, 25–75 IQR of 10, 7–15.8mm vs 4, 3–8mm), and had better preserved cellular architecture and tissue integrity. Crush artefacts were less common with CB (2/22) compared with FFB (21/22). No significant bleeding was reported. Conclusions CB during flexi‐rigid pleuroscopy is feasible, safe and effective. Its routine use during flexi‐rigid pleuroscopy requires further evaluation.